2007
DOI: 10.1644/06-mamm-f-185r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines of the American Society of Mammalogists for the Use of Wild Mammals in Research

Abstract: Guidelines for use of wild mammal species are updated from the American Society of Mammalogists (ASM) 2007 publication. These revised guidelines cover current professional techniques and regulations involving mammals used in research and teaching. They incorporate additional resources, summaries of procedures, and reporting requirements not contained in earlier publications. Included are details on marking, housing, trapping, and collecting mammals. It is recommended that institutional animal care and use comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
547
0
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,212 publications
(563 citation statements)
references
References 21 publications
2
547
0
14
Order By: Relevance
“…Several research programs depend upon safe handling procedures under field conditions to mark, measure, vaccinate, or sample wild animals (Gannon and Sikes, 2007). The efficacy of chemical immobilization depends on the type of drug, dose, season, species, and characteristics including sex, age, and size of target animals (Jalanka and Roeken, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Several research programs depend upon safe handling procedures under field conditions to mark, measure, vaccinate, or sample wild animals (Gannon and Sikes, 2007). The efficacy of chemical immobilization depends on the type of drug, dose, season, species, and characteristics including sex, age, and size of target animals (Jalanka and Roeken, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…With the method described here we showed that manipulation can be minimized and blood collection in fully conscious animals requires less than 1 min. Because of that, when collecting blood samples in armadillos in field studies, if the pain is minimal and quick, anesthesia is not recommended because the animal can be released immediately (Gannon & Sikes 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no studies about the injure impact of cardiac puncture in armadillos, although it has been demonstrated to be a detrimental procedure that can shorten the life in other species (Moore 1983), and therefore its application is controversial. On the other hand, the obligatory use of anesthesia generates another disadvantage of the method (Gannon & Sikes 2009) and makes its use inadvisable when a large population of samplings is required.…”
Section: Introductionmentioning
confidence: 99%
“…Contact with domestic animals is limited but not impossible, particularly with free roaming feral cats, because there are no barriers limiting the access to the park. ANIMAL TRAPPING Animals were handled according to the American Society of Mammalogists recommendations (Gannon et al 2007) Coatis were captured by sedation with a dart shot using a blowgun at 2 to 4 meters away from the animal. Chemical restraints were performed with 40 to 100 mg/individual of ketamine chlorohydrate (Pisa-Agropecuaria, Guadalajara, JAL, Mx) and 2 to 4 mg/ individual xylazine (Pisa-Agropecuaria, Guadalajara, JAL, Mx).…”
Section: Area Of Study and Animal Populationmentioning
confidence: 99%